2004
DOI: 10.1074/jbc.m305790200
|View full text |Cite
|
Sign up to set email alerts
|

Response of Human Pulmonary Epithelial Cells to Lipopolysaccharide Involves Toll-like Receptor 4 (TLR4)-dependent Signaling Pathways

Abstract: Pulmonary epithelial cells are continuously exposed to microbial challenges as a result of breathing. It is recognized that immune myeloid cells express Toll-like receptors (TLRs), which play a major role in detecting microbes and initiating innate immune responses. In contrast, little is known concerning the expression of TLR in pulmonary epithelial cells per se, their distribution within the cell, their function, and the signaling pathways involved. In this work, we demonstrated by reverse transcription-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
255
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(287 citation statements)
references
References 37 publications
(40 reference statements)
27
255
1
4
Order By: Relevance
“…However, only limited information is available for the situation in the upper airways. It has been reported that the sensitivity and the activation threshold of TLR in bronchial epithelial cells is indeed regulated [6,[14][15][16], supporting the concept that airway epithelial cells actively restrict pattern recognition principles.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, only limited information is available for the situation in the upper airways. It has been reported that the sensitivity and the activation threshold of TLR in bronchial epithelial cells is indeed regulated [6,[14][15][16], supporting the concept that airway epithelial cells actively restrict pattern recognition principles.…”
Section: Introductionmentioning
confidence: 81%
“…This has two important implications: First, epithelial cells at non-sterile surfaces have to regulate their TLR sensitivity to avoid continuous threat of inflammation and, second, organ-specific mechanisms of regulating immunity have to exist. The first fact has now been intensively studied and multiple mechanisms including threshold regulation of TLR stimulation [6,10], anatomical sequestration [14,26], inhibitory signaling molecules [27,28], coreceptor modulation [6] and specific signaling pathways [29] have been described. The second hypothesis was the subject of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Other epithelial cell types (e.g. bronchial epithelial cells [18], nasopharynx epithelial cells [48], etc.) have also been shown to respond to LPS.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 However, not all of these TLRs and the associated adaptors are equally available on the surface of the airway epithelium where they can respond to luminal contaminants. Whereas TLR2 is apically expressed and TLR5 is readily mobilized in response to bacteria, 5,6 TLR4 is intracellular 11 and is not mobilized to the cell surface in response to the major lung pathogens P. aeruginosa or S. aureus. 5 The expression of MD2, a co-stimulatory molecule that it is required for TLR4 signaling, is limited on airway epithelial cells 11 which explains the minimal response to LPS.…”
Section: Bacterial Recongnition By Airway Epithelial Cellsmentioning
confidence: 99%